A study of the relationships between strategic planning practices and perceived school excellence - Mohd Ali, Hairuddin; Ayodele, Lasisi Abass (2011)
This study attempts to examine the extent of the practice of strategic planning at International Islamic School (IIS), a sub-business unit of International Islamic University Malaysia. The main objective of this study is to investigate the extent IIS practice strategic planning for school excellence. For this purpose, a set of questionnaires using five point Likert Scale was designed to get information from the targeted respondents comprised the top executives and members of the strategic planning team of IIS. The study mainly used the descriptive statistics for data analysis. The main finding of the study confirmed that IIS practiced all five processes of strategic planning for school excellence.